TECHNICAL LEADERSHIP AND ARCHITECTURAL DEBT MANAGEMENT IN LARGE SOFTWARE ECOSYSTEMS (American Journal of Technology and Applied Sciences, 2025)
This article examines the role of technical leadership in managing architectural debt in large software ecosystems. It analyzes the root causes of architectural debt, its impact on development quality and cost, and organizational and architectural practices that can help manage and mitigate its negative effects. Particular attention is paid to the relationship between architectural decisions, strategic management, and the culture of engineering leadership.